Mitochondrial Dysfunction in Endothelial Progenitor Cells: Unraveling Insights from Vascular Endothelial Cells - Azra Kulovic-Sissawo; Carolina Tocantins; Mariana S. Diniz; Elisa Weiss; Andreas Steiner; Silvija Tokic; Corina T. Madreiter-Sokolowski; Susana P. Pereira; Ursula Hiden (Biology, 2024)
Endothelial dysfunction is associated with several lifestyle-related diseases, including cardiovascular and neurodegenerative diseases, and it contributes significantly to the global health burden. Recent research indicates a link between cardiovascular risk factors (CVRFs), excessive production of reactive oxygen species (ROS), mitochondrial impairment, and endothelial dysfunction. Circulating endothelial progenitor cells (EPCs) are recruited into the vessel wall to maintain appropriate endothelial function, repair, and angiogenesis. After attachment, EPCs differentiate into mature endothelial cells (ECs). Like ECs, EPCs are also susceptible to CVRFs, including metabolic dysfunction and chronic inflammation. Therefore, mitochondrial dysfunction of EPCs may have long-term effects on the function of the mature ECs into which EPCs differentiate, particularly in the presence of endothelial damage. However, a link between CVRFs and impaired mitochondrial function in EPCs has hardly been investigated. In this review, we aim to consolidate existing knowledge on the development of mitochondrial and endothelial dysfunction in the vascular endothelium, place it in the context of recent studies investigating the consequences of CVRFs on EPCs, and discuss the role of mitochondrial dysfunction. Thus, we aim to gain a comprehensive understanding of mechanisms involved in EPC deterioration in relation to CVRFs and address potential therapeutic interventions targeting mitochondrial health to promote endothelial function.